Identity reflexivity: a framework of heuristics for strategy change in hybrid organizations. Issue 7 (3rd June 2021) - Greco, Angela; Long, Thomas; de Jong, Gjalt
Abstract : Purpose: The aim of this research is to investigate the relationship between (dual) organizational identity and individual heuristics – simple rules and biases – in the process of strategy change. This paper offers a theory on identity reflexivity as a cognitive mechanism of strategy change in the context of organizational hybridity. Design/methodology/approach: The authors draw on a 2-year ethnographic study at a Dutch social housing association dealing with the process of strategy change. The empirical data comprises of in-depth semi-structured interviews, ethnographic observations as well as secondary sources. Findings: Conflicting identities at the organizational level influence heuristics at the individual level, since members tend to identify with their department's identity. Despite conflicting interpretations, paths of cognitive shortcuts – that the authors define as internal and external identity reflexivity – are shared by the conflicting identities. Research limitations/implications: The findings of this research are subject to limitations typical of a qualitative case-study, such as possibly being context dependent. The authors argue that this research contributes to the understanding of how individual heuristics relate to organizational heuristics, and suggest that the process of identity reflexivity can contribute to the alignment of conflicting identities enabling strategy formation in the context of a dual-identity organization. Practical implications: Understanding how managers with conflicting identities achieve agreements is important to help organizational leaders to pursue sustainability-oriented strategy change. Social implications: Given the pressure experienced by mission-driven organizations to integrate multiple sustainability demands in their mission, understanding managers' decision-making mechanism when adapting to new, often conflicting, sustainability demands is important to accelerate societal sustainability transitions. Originality/value: This paper addresses the process of new strategy design in the context of a socially driven business. This context fundamentally differs from the one addressed by the existing heuristics literature with respect to organizational environment and role, and specific competing demands.